Помилки та ризик у хірургічному лікуванні вторинного гіперпаратиреозу - Ларін, О. С.; Черенько, С. М.; Ткаченко, Р. П. (Clinical Endocrinology and Endocrine Surgery, 2010)
Early diagnosis of secondary hyperparathyroidism in patients with chronic renal failure will permit to avoid the unjustified delay of surgical treatment, to decrease the risk of complication and to improve patient quality of life and life span.